(untitled) (Palíndromo, 2021)
Based on fragments of an autobiographical cut, the text seeks, not to answer, but to dialogue with the question proposed by the editor: "what motivates me/us/you in art?". From the perspective of Heidegger’s phenomenology, it starts from the ontological analysis of Being-in, the way of being of the being that we are, in its constituent aspects, to extend it to the being of the artist and of art. To do so, it seeks to extend the dialogue to genealogies that electively affect the author in his practical and theoretical relationship with art, as well as with the contextual conditions that involve the production, circulation and reception of art work in contemporary society, its limits and contingencies . Finally, it looks at the current and recent moment of its author’s work, in order to dive in search of the interests and motivations that lead to its realization, as well as to the transit between languages of the expanded field of art and related fields.